Negative Symptoms Management in Schizophrenia - Maria Francisca Intan Primasiwi Lolobua; Khairina Khairina; Ida Aju Kusuma Wardani; Angelina M. Mirna Santoso (Jurnal Psikiatri Surabaya, 2021)
Clinicians often overlook the presence of negative symptoms in treating schizophrenia. The burden borne by patients, families, and society is quite heavy. These symptoms not only have high costs, but also affect the functional prognosis in independence and socializing. There is a need for adequate therapy of negative symptoms of schizophrenia which can improve the patient’s quality of life. Negative symptoms are characterized by blunt affect, alogia, avolition, anhedonia, and asociality. Knowing the difference between the primary and secondary types of negative symptoms of schizophrenia can bring big impact on the therapy. The primary type of negative symptoms is an integral part of schizophrenia, while the secondary one is caused by external conditions of schizophrenia, such as depression. Management of negative symptoms of schizophrenia includes psychopharmaceuticals and non-psychopharmaceuticals. Atypical antipsychotics remain the drug of choice due to their affinity not only to D2 receptor, but also to serotonin, glutamate, histamine, α adrenergic, and muscarinic receptors. In addition, the higher dissociation rate of D2 receptors of atypical antipsychotics allow for minimal motor side effect. Cariprazine has been approved by The Food and Drug Associaton and The European Medicines Agency to treat primary and persistent negative symptoms due to its minimal side effect. Non-pharmacological therapies such as Cognitive Behavioral Therapy (CBT) and Motivation and Engagement Training (MOVE) can optimize the treatment efficacy. These therapies will enhance the cognitive improvement, adaptation, and social skill development of the patients.